Multi-Parametric Field Experiment Links Explosive Activity and Persistent Degassing at Stromboli - Thivet, Simon; Harris, Andrew J. L.; Gurioli, Lucia; Bani, Philipson; Barnie, Talfan; Bombrun, Maxime; Marchetti, Emanuele (Frontiers in Earth Science, 2021)
Visually unattainable magmatic processes in volcanic conduits, such as degassing, are closely linked to eruptive styles at the surface, but their roles are not completely identified and understood. To gain insights, a multi-parametric experiment at Stromboli volcano (Aeolian Islands, Italy) was installed in July 2016 focusing on the normal explosive activity and persistent degassing. During this experiment, gas-dominated (type 0) and particle-loaded (type 1) explosions, already defined by other studies, were clearly identified. A FLIR thermal camera, an Ultra-Violet SO₂ camera and a scanning Differential Optical Absorption Spectroscopy were deployed to record pyroclast and SO2 masses emitted during individual explosions, as well as persistent SO₂ fluxes, respectively. An ASHER instrument was also deployed in order to collect ash fallouts and to measure the grain size distribution of the samples. SO2 measurements confirm that persistent degassing was far greater than that emitted during the explosions. Further, we found that the data could be characterized by two periods. In the first period (25–27 July), activity was mainly characterized by type 0 explosions, characterized by high velocity jets. Pyroclast mass fluxes were relatively low (280 kg/event on average), while persistent SO2 fluxes were high (274 t/d on average). In the second period (29–30 July), activity was mainly characterized by type 1 explosions, characterized by low velocity jets. Pyroclast mass fluxes were almost ten times higher (2,400 kg/event on average), while persistent gas fluxes were significantly lower (82 t/d on average). Ash characterization also indicates that type 0 explosions fragments were characterized by a larger proportion of non-juvenile material compared to type 1 explosions fragments. This week-long field experiment suggests that, at least within short time periods, Stromboli’s type 1 explosions can be associated with low levels of degassing and the mass of particles accompanying such explosive events depends on the volume of a degassed magma cap sitting at the head of the magma column. This could make the classic particle-loaded explosions of Stromboli an aside from the true eruptive state of the volcano. Instead, gas-dominated explosions can be associated with high levels of degassing and are indicative of a highly charged (with gas) system. We thus suggest that relatively deep magmatic processes, such as persistent degassing and slug formation can rapidly influence the superficial behavior of the eruptive conduit, modulating the presence or absence of degassed magma at the explosion/fragmentation level.